Carbon allocation traits are coordinated across plant organs, yet dry matter content is decoupled in three Mediterranean woody species - Gianluigi Ottaviani; Marta Magnani; Heath Beckett; Carlo Calfapietra; Mauro Lo Cascio; Mathieu Millan; Irene Tunno; Carlotta Volterrani; Silvia Portarena; Angelino Carta (Plant and Soil, 2026)
Background and aims Trait-based functional ecology often assumes that plant organs (e.g. leaf, stem, root) having dense tissues (high dry matter content; DMC) are carbon (C)-expensive. However, this assumption remains largely untested. Here, we examine whether 1) C-allocation traits co-vary forming coordinated functional strategies, 2) isotopic composition of leaf carbon (δ 13 C) can be effectively traced across organs and can estimate C present in upper soil layers thereby forming a plant-soil continuum, and 3) easy-to-collect traits can predict key soil ecosystem functions (C stock, nutrient status). Methods We focused on three widely distributed Mediterranean woody species ( Cistus salviifolius, Erica arborea , Quercus ilex ), measuring plant traits and soil parameters from three sites in Italy. We applied a Bayesian analytical framework considering the co-varying effects of biotic (species, developmental stage) and abiotic (site, fire disturbance) factors. Results Trait co-variation indicates integrated functional strategies for C allocation, especially for δ 13 C across organs. However, DMC of different organs is decoupled from %C and δ 13 C of the relative organ. We find no evidence for the occurrence of a δ 13 C plant-soil continuum, nor for easy-to-collect traits to predict soil functions. Conclusion The widely assumed positive relationship between DMC and C investment does not emerge in the three focal Mediterranean woody species, suggesting within-organ water content regulation as a key morpho-physiological adjustment in our model system. While the focal species are representative of the phylogenetic and functional variation in the Mediterranean woody flora, the generality of our findings should be tested in other regions hosting mediterranean-type ecosystems.

Determining the age of clonal plants: challenges and prospects - Jitka Klimešová; Patrik Mráz; Beata Oborny; Timothy Harris; Gabriela Santos da Silva; Alexandre Ferraro; Jiří Doležal; Mathieu Millan (Trends in Ecology & Evolution, 2026)

Ligno-aliphatic complexes in soils revealed by an isolation procedure: implication for lignin fate - Mathieu Thevenot; Marie-France Dignac; Mercedes Mendez-Millan; Haithem Bahri; Christine Hatté; Gérard Bardoux; Cornelia Rumpel (Biology and Fertility of Soils, 2013)